Studi Kualitatif tentang Pola Konsumsi pada Ibu Hamil Kekurangan Energi Kronis di Desa Batuputih Laok - Fadzilah, Rochmanita Ilvanadewi; Yuliatik, Ita; Puspikawati, Septa Indra; Mahiroh, Hodimatum (Universitas Airlangga, 2024)
Background: hronic Energy Deficiency (CED) is a nutritional problem that often occurs in pregnant women due to chronic energy deficiency over a long period of time. Chronic Energy Deficiency (CED) in developing countries is the cumulative result of a state of malnutrition since the fetal period, infancy, and childhood that can continue into adulthood. Pregnant women with CED are at risk of giving birth to babies with low birth weight (LBW). Objective: This study aims to analyze the causes of Chronic Energy Deficiency (CHD) in pregnant women in Batuputih Laok Village. Method: This research method is qualitative with a descriptive research design through a phenomenological approach. The research subjects ware taken purposively. The research subjects ware pregnant woman with anemia in Batuputih Laok Village as key informants with a total of 6 people. Results: Informants have an age range of 20-29 years with elementary, high school, and D3 education. All informants had anemia and LILA <23.5 cm so they were classified as SEVERE. In addition, the results of the in-depth interview showed that pregnant women did not want to consume foods with balanced nutrition during their pregnancy. In addition, pregnant women did not consume fish and other proteins because they did not like the fishy smell and there were restrictions on fish consumption. Some informants sometimes only eat one meal a day even though they are pregnant. Informants did not take Fe because they did not like taking medicine, and there were informants who did not take Fe during their five-month pregnancy due to nausea. Conclusion: CED in pregnant women is caused by consumption patterns that do not want to consume high-protein foods, the existence of taboos from parents, food menus that are not diverse, food portions that are less than calorie needs, lack of meal frequency, and not taking Fe. Therefore, there is a need for counseling and nutritional counseling for pregnant women to increase knowledge about the importance of balanced nutrition for pregnant women and to correct misconceptions about food abstinence.